Choice and competition in the welfare state: Home care as the ideal quasi-market - Mats A. Bergman; Henrik Jordahl; Sofia Lundberg (Research Institute of Industrial Economics (IFN), 2018)
We study a reform by which a standardized model of choice and competition was introduced in tax-financed home care in a majority of Swedish municipalities. The market for home care is of particular interest since it is close to the ideal quasi-market. For identification, we exploit the different timing of reform implementation across municipalities. We find that the introduction of free choice and free entry in home care increased perceived quality by about one quarter of a standard deviation without affecting costs. Since satisfaction is unrelated to the private market share, the underlying mechanism seems to be new choice opportunities rather than competition or an advantage of private providers.
Keywords: H42; H75; I11; L33; 330; Choice; Competition; Privatization; Elderly care; New public management